Control of Post harvest waste of “Capsicum annuum” by Application of Natural Polymer glazer (International Journal of Food and Nutritional Sciences, 2023)
Thus, the application of mucilage as a natural polymers, extracted from the waste flowersof avenue roadside plants would be helpful in maintaining the quality of harvested vegetables aswell as it might be helpful to reduce the losses caused during post harvest transport. The naturalcoater was prepared with the application of mucilage powder along with protein, lipidcomplexes.